Model of sustainability of SMEs in V4 countries - Zvarikova, Katarina; Dvorsky, Jan; Belas, Jaroslav Jr.; Metzker, Zdenko (Journal of Business Economics and Management, 2024)
The research’s objective was to develop a thorough model of the viability of SMEs in the V4 countries based on predetermined variables. The following factors were defined: human resources management, business ethics, corporate social responsibility, company digitalisation, environmental considerations, financial management, and sustainability of SMEs. The model was developed on the solid empirical research carried out in the Visegrad Four countries in June 2022 by the renowned external agency MNFORCE using a sample of 1,398 respondents and the “Computer Assisted Web Interviewing” technique. According to the research, the developed complex model of SMEs’ sustainability depending on the listed criteria is statistically significant. Each investigated factor has a favourable impact on SMEs’ sustainability. The study’s findings supported the notion that the environmental aspects of the business have the strongest positive impact on the long-term sustainability of SMEs. The study’s findings indicate that the management of human resources, finances, and the degree of digitalisation of SMEs significantly influence the viability of businesses. The findings provide an important platform for managers responsible for the sustainability of the SME segment at the worldwide level (International council for small business), national level (particularly for V4 nations), as well as institutions supporting SMEs and SME owners.